Translation and Appropriation: Greek Relics in the Latin West in the Aftermath of the Fourth Crusade - Lester, Anne Elisabeth (Studies in church history, 2017)
Following the fall of Constantinople to French, Flemish and Venetian forces at the conclusion of the Fourth Crusade, an unprecedented number of relics and other holy objects poured into the West between 1204 and c.1240. Sent as personal and diplomatic gifts, most holy objects moved in the open, with letters of authentication and identification, and not (as has often been suggested) as sacred theft. This article traces the work of translation, carried out by clerics, chaplains, monks, and laymen and women, and the mechanisms of appropriation that gave meaning to these objects in their new devotional contexts. Relics were demanding things; they needed to be enshrined, venerated, described and contextualized, and their movements needed to be accounted for and included within a broader Christian narrative that served to anchor the crusade movement to the apostolic past and to Christ's material presence in the West. Moreover, the materiality of the relics that moved from Constantinople was an important part of their significance and shaped devotional practices and connections, bridging differences between Greek and Latin culture and fostering conceptions of the material that facilitated other acts of Christian translation in the centuries to come.